Determination of long-term permissible currents in wires of power supply systems of railways - E. P. FIGURNOV; Yu. I. ZHARKOV; V. I. KHARCHEVNIKOV (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
In the standard for contact wires made from copper and its alloys, the values of long-term permissible temperatures have significantly decreased. This requires recalculation of previously valid values of long-term permissible currents. Authors considered revised method for calculating the long-term permissible currents, based on a more rigorous consideration of the laws of heat transfer and experimental studies of the conditions of heating and cooling of shaped (contact) and stranded wires. Technique is based on heat balance conditions, using which the sources of greatest inaccuracies become such quantities as cooled surface area, influence of wind direction, meteorological conditions, laws of change in heat transfer coefficient, effect on additional heating of solar radiation. Deviations when these indicators are taken into account by existing methods can cause errors of 40 % or more. Formulas for calculating the actual outer surface of stranded and shaped wires are given. The inadmissibility of calculating the surface area of the wires by their reference diameter is noted. Updated law of the change in heat transfer coefficient for stranded and shaped wires, as well as the degree of its dependence on wind speed and cooled surface, is given based on a summary of extensive domestic and foreign research. It is shown that with the longitudinal direction of the wind, the reduction of this coefficient occurs to a lesser extent than has been assumed so far. Authors propose method for taking into account an increase in the heat transfer coefficient under meteorological conditions characteristic of ice formation. The heat transfer coefficient of shaped and stranded wires in no case can not be taken as for round pipes with smooth surface. Existing method of accounting for solar radiation, which influences the additional heating of wires, leads to an unjustified and repeated exaggeration of this effect, since previously only the radiation incident on the wire was taken into account in the calculations. According to the laws of heat transfer, the temperature of the irradiated body does not depend on the incident, but on the resulting radiation, defined as the difference between the radiations incident on the body and emitted by it in accordance with its temperature. A formula for accounting for such heat transfer is proposed. The above methodology and calculation formulas allow performing reasonable calculations to determine the long-term permissible currents of individual stranded and shaped wires, as well as the contact network as a whole.